China: Anti-Crisis Potential of the Economy and its Impact on the Social Sphere - Krekova, Marina M.; Tupchienko, Vitaly A.; Zhagparova, Aida O.; Lisichkina, Yulia S.; Novikov, Vladimir S.; Kramarenko, Elena R. (International Journal of Economics and Financial Issues, 2016)
The article deals with some aspects of the global financial crisis on China's economic and social development. It describes the main indicators of the economy before and after the crisis. Also, analysis of the main sectors that experienced the greatest impact of the global financial crisis. Identified and grouped measures of anti-crisis development of the PRC, which contribute to overcoming the consequences of the crisis as soon as possible. The financial crisis is strong enough impact on the socio-economic development of the PRC. This affected the decrease in real income of the population and led to curb economic growth. Also, the well-being of the population decreased significantly, due to the reduced capacity of the current consumption, investment and the creation of savings of the population, impairment of financial capital and devaluation of the dollar. Keywords: socio-economic development, world financial crisis, socio-economic implications, social sphere, anti-crisis JEL Classifications: A14, H12, F63